Housewives’ lifestyle and behavior of debt dependency on bank thitil - Suciawati Khusnul Khotimah; Ketut Prasetyo; Sukma Perdana Prasetya; Nasution Nasution (Faculty of Social and Political Science, Universitas Airlangga, 2022)
The fulfillment of household needs can implement various strategies, including debt strategy. A money lending service becomes an attraction to fulfilling the needs of life. The money lending service on credit is known as bank thitil by Javanese. This study presents the factors that make housewives have a dependency behavior on bank thitil loans. This dependency behavior is examined from the perspective of the planned behavior theory by Ajzen. This study used a qualitative approach and the subjects of this study were housewives who have debt in bank thitil. Some factors encourage the dependency behavior of housewives on bank thitil loans. This research finds that the implementation of Ajzen’s planned behavior theory in analyzing the factors of indebted housewives is integrated with some factors, including (1) the influence of attitudes that assume the bank thitil provides benefits, (2) subjective norms in the form of lifestyle and environmental vicinity, and (3) social control that supports the housewives in borrowing money from the bank thitil.